Antagonism Between DUX4 and DUX4c Highlights a Pathomechanism Operating Through β-Catenin in Facioscapulohumeral Muscular Dystrophy - Ganassi, Massimo; Figeac, Nicolas; Reynaud, Magalie; Ortuste Quiroga, Huascar Pedro; Zammit, Peter S. (Frontiers in Cell and Developmental Biology, 2022)
Aberrant expression of the transcription factor DUX4 from D4Z4 macrosatellite repeats on chromosome 4q35, and its transcriptome, associate with pathogenesis in facioscapulohumeral muscular dystrophy (FSHD). Forced DUX4 expression halts skeletal muscle cell proliferation and induces cell death. DUX4 binds DNA via two homeodomains that are identical in sequence to those of DUX4c (DUX4L9): a closely related transcriptional regulator encoded by a single, inverted, mutated D4Z4 unit located centromeric to the D4Z4 macrosatellite array on chromosome 4. However, the function and contribution of DUX4c to FSHD pathogenesis are unclear. To explore interplay between DUX4, DUX4c, and the DUX4-induced phenotype, we investigated whether DUX4c interferes with DUX4 function in human myogenesis. Constitutive expression of DUX4c rescued the DUX4-induced inhibition of proliferation and reduced cell death in human myoblasts. Functionally, DUX4 promotes nuclear translocation of β-CATENIN and increases canonical WNT signalling. Concomitant constitutive expression of DUX4c prevents β-CATENIN nuclear accumulation and the downstream transcriptional program. DUX4 reduces endogenous DUX4c levels, whereas constitutive expression of DUX4c robustly suppresses expression of DUX4 target genes, suggesting molecular antagonism. In line, DUX4 expression in FSHD myoblasts correlates with reduced DUX4c levels. Addressing the mechanism, we identified a subset of genes involved in the WNT/β-CATENIN pathway that are differentially regulated between DUX4 and DUX4c, whose expression pattern can separate muscle biopsies from severely affected FSHD patients from healthy. Finally, blockade of WNT/β-CATENIN signalling rescues viability of FSHD myoblasts. Together, our study highlights an antagonistic interplay whereby DUX4 alters cell viability via β-CATENIN signalling and DUX4c counteracts aspects of DUX4-mediated toxicity in human muscle cells, potentially acting as a gene modifier for FSHD severity. Importantly, direct DUX4 regulation of the WNT/β-CATENIN pathway informs future therapeutic interventions to ameliorate FSHD pathology.